Using national laboratory data to assess cumulative frequency of linkage after transfer to community‐based HIV clinics in South Africa. Issue 6 (27th June 2019) - Bassett, Ingrid V; Huang, Mingshu; Cloete, Christie; Candy, Sue; Giddy, Janet; Frank, Simone C; Freedberg, Kenneth A; Losina, Elena; Walensky, Rochelle P; Parker, Robert A
Abstract: Introduction: Changes to the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) funding have led to closures of non‐governmental HIV clinics with patient transfers to government‐funded clinics. We sought to determine the success of transfers in South Africa using a national data source. Methods: All adults (≥18 years) on antiretroviral therapy (ART) who visited a single PEPFAR‐funded hospital‐based HIV clinic in Durban, South Africa from March to June 2012 were transferred to community‐based clinics. Previously, we matched patient records from the hospital‐based HIV clinic with National Health Laboratory Services (NHLS) Corporate Data Warehouse (CDW) data to estimate the proportion of patients with a CD4 count or viral load (VL) in the CDW during the year before transfer. As a proxy for retention in care, in this study we evaluated whether patients had a CD4 count or VL at another facility within approximately three years of transfer. Patients referred to a private doctor at transfer were excluded from the analysis. We assessed predictors (age, sex, CD4 count, VL status, ART duration and location of future care) of not having post‐transfer laboratory data using Cox proportional hazards models. Results: Of the 3893 patients referred to a government facility at transfer, 41% were male and median age was 39 years (IQR 34 to 46). There was a post‐transfer CD4 count or VL from another facility for 23% of these individuals within six months, 44% within one year, 57% within two years and 61% within approximately three years. Male sex (aHR 1.20, 95% CI 1.10 to 1.31) and shorter duration on ART (<3 months, aHR 3.80, 95% CI 2.77 to 5.21; three months to one year, aHR 1.32, 95% CI 1.15 to 1.51, each compared with >1 year) were associated with not having a post‐transfer record. Conclusions: Using data from the NHLS CDW, 61% of patients had evidence of a post‐transfer laboratory record at another facility within approximately three years after closure of a large South African HIV clinic. Males and those with shorter time on ART prior to transfer were at highest risk for lacking follow‐up laboratory data. As patients transfer care, national data sources can be used to evaluate long‐term patient care trajectories.